Effects of 45S5 bioactive glass on the remineralization of early carious lesions in deciduous teeth: an in vitro study - Rui Zhang; Jianyan Qi; Min Gong; Qian liu; Hongyan Zhou; Jue Wang; Yufeng Mei (BMC, 2021)
Abstract Background Early childhood caries has been designated as a serious public health problem. The traditional restoration method is very challenging, especially in uncooperative patients. Non-invasive therapy, like remineralization agents, which have been developed to reverse the demineralization progress at the early stage of caries, may be a better choice. This study aimed to evaluate the remineralization efficacy of different concentrations of 45S5 bioactive glass (BAG) on artifical carious lesions of deciduous enamel. Methods 65 caries-like enamel lesions of the deciduous teeth were assigned to 5 groups (n = 13) and transported to a 14 days pH-cycling: Group A: 2%BAG, Group B: 4%BAG, Group C: 6%BAG, Group D: 8%BAG, and Group E: deionized water (DDW, negative control). 8 sound (Group F) and 8 demineralized teeth (Group G) were prepared for contrast. The recovery power of mechanical property was evaluated by Vickers hardness test through the recovery of enamel microhardness (%REMH). Surface morphology, mass fraction of Ca and P ions, and Ca/P atomic ratio were analyzed by scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (EDX). Moreover, Fourier transform infrared spectroscopy equipped with attenuated total reflectance was used to identify the chemical structure of newly formed compounds. Results % REMH were (42.65 ± 1.35), (52.59 ± 2.96), (57.40 ± 1.72), (52.91 ± 2.55), (12.46 ± 2.81) in 2%BAG, 4%BAG, 6%BAG, 8%BAG, and DDW groups respectively. Micro-spherical particles were deposited in all BAG groups and 6% BAG showed the densest and most uniform surface. EDX analysis identified significantly higher Ca(wt%) and P(wt%) in four BAG groups than in the demineralized group (p < 0.005), while 6% BAG showed the highest mineral gain efficacy. The infrared spectrum demonstrated that newly mineralized crystals were consisted of type-B hydroxycarbonate apatite. Conclusion BAG possessed a promising remineralization effect on artificial lesions in deciduous enamel by recovering enamel surface mechanical property, morphology and chemical elements. Among them, 6% BAG performed the greatest overall efficacy. Acting as a new caries-arresting biomaterial, 45S5 BAG has the potential to facilitate the adaptation of better carious prevention strategies in children.